KINERJA PROTOKOL NETWORK REDUNDANSI VRRP, HSRP DAN GLBP PADA LAYANAN VIDEO STREAMING - I Putu Gede Krsna Yudha Dharma; Pande Ketut Sudiarta; Widyadi Setiawan (Jurnal SPEKTRUM, 2021)
Nowadays streaming video services have become the main need for internet users. Tokeep the streaming video service awake, an alternative path is needed to avoid network failure.In creating an alternative path, you can use first hop redundancy protocol (FHRP). In FHRPthere are three redundancy protocols including VRRP, HSRP and GLBP. The purpose of thisstudy is to find out better protocol performance, especially by using streaming video services.The method used is to simulate redundancy protocol using GNS-3 software with 3 scenariosthat run including normal network, down network and recovery network. As for testing eachscenario including testing routers with priority, route trace route, link transfer time and quality ofservice (QoS) video streaming. Based on the results of the study, it was obtained that GLBPprotocol has better performance with an average link transfer time of 1.51 seconds, delay of8.12 ms, packet loss of 0 % and throughput of 1,248 Mbps. This is because in GLBP protocolthere is a load balancing feature that can split the load equally and utilize resources moreeffectively from each router.